Micronised Biomass Silica as cement replacement material in concrete - Suraya Hani, Adnan; Lee, Yee Loon; Ismail, Abdul Rahman; Hamidah, Mohd Saman; Hanita, Yusof (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology (MUCEET) 2009, 20th - 22nd June 2009 organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis at MS Garden,Kuantan, Pahang, Malaysia.